2022
DOI: 10.7759/cureus.30898
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Postpartum Depression

Abstract: Postpartum depression (PPD) is a widespread mental health problem and one of the prime causes of maternal suffering and ill health. On a global level, the prevalence of the disorder is about 10 to 15%. Symptoms generally appear within the first four to six weeks, which is the high-risk period. However, it may develop up to one year post-delivery. PPD presents with symptoms of classical depression, including mood fluctuations, bouts of crying, lack of interest in the child, and even thoughts of suicide. PPD not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Furthermore, our findings demonstrated that social support and postpartum quality of life were mutually dependent. These results are consistent with previous studies, including review or meta-analysis studies with random- effects model, which have identified a lack of social support as a major risk factor for PPD [ 49 – 51 , 54 , 55 ]. Riem et al’s review study also supports our results, as it found that low social support is associated with self- reported mental disorders symptoms, such as stress and anxiety, during postpartum [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our findings demonstrated that social support and postpartum quality of life were mutually dependent. These results are consistent with previous studies, including review or meta-analysis studies with random- effects model, which have identified a lack of social support as a major risk factor for PPD [ 49 – 51 , 54 , 55 ]. Riem et al’s review study also supports our results, as it found that low social support is associated with self- reported mental disorders symptoms, such as stress and anxiety, during postpartum [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that there is an increase in maternal attachment due to the decrease in depression during pregnancy and the postpartum period 29,30 . It has been observed that a proportion of women with postpartum depression also have depression during pregnancy and that this effect is maintained in the postpartum period 31,32 . In this context, assessing mothers for postpartum depression risk during pregnancy and taking appropriate precautions for at‐risk groups will have positive outcomes for both postpartum depression and maternal attachment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having adverse effects on mothers’ health for several months or even one year, PPD may also have serious consequences for children and families ( 3 , 4 ). PPD is not conducive to forming a healthy mother−child relationship which is important for child development and may affect maternal attachment, sensitivity and parenting style, making children more prone to malnutrition and delaying development ( 5 , 6 ). PPD patients are at increased risk of developing depressive episodes in the future and are more likely to be diagnosed with bipolar disorder ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, various environmental or genetic risk factors that may lead to PPD have been comprehensively studied, but the etiology and pathophysiology of PPD are not fully understood ( 9 ). The powerful risk factors for PPD include a history of psychiatric illness, such as depression; gestational diabetes; risky pregnancy; domestic violence; and lack of social support ( 5 , 10 , 11 ).These risk factors for PPD reduce individuals’ ability to cope with crisis conditions and increase susceptibility to stress. Stress and previous adverse life events, which are associated with neuroendocrine changes, are important risk factors for PPD ( 12 ).…”
Section: Introductionmentioning
confidence: 99%